اعادة تاهيل قصر الجعار لبازار ومعرض تجاري وسط مدينة بيت لحم - رزمق, تمارة (جامعة بوليتكنك فلسطين - معماري, 2019)
The traditional architecture in Palestine is exposed to a various types of destruction and distortion. In addition to the destruction caused by the Israeli occupation for the historical centers and buildings in Palestine, the main reason returns to neglecting these buildings and abandonment it to the nature to fallout and gone. The problem lies in the existence of many traditional buildings such as the al Jaar palace building in the city of Bethlehem, which tells the story of the entire nation neglected for a long time and almost disappear with time. The building needs to be rehabilitated in manner commensurate with the development of civilization in the region as a commercial center and the fact that the location of the palace in the center of the city of Bethlehem, where the strongest commercial movement caused the choice of rehabilitation to a shopping center and the absence of a traditional building converted into a shopping building, that makes project unique in the region and restore the spirit of Palestinian life and preserve the Palestinian cultural heritage. Through the study of some relevant references, use of information available, and collect information from some websites, and visit some concerned authorities, has been determined the type of research methodology that is based on quantitative and qualitative research. To achieve the research objectives, The research has been studied design and planning standards for buildings rehabilitation, More than one case study were analyzed to determine the weaknesses and strengths for each to be used and avoided in the design process, then the site location was analyzed to determine the potentials that will help in XV determining the need for the project, then the project requirements have been identified by analysis the function of project.
CD , no of pages 104 , معماري 3/2019
Keywords: تأهيل المباني